2016
DOI: 10.1038/eye.2016.241
|View full text |Cite
|
Sign up to set email alerts
|

Agreement and clinical comparison between a new swept-source optical coherence tomography-based optical biometer and an optical low-coherence reflectometry biometer

Abstract: PurposeTo compare measurements taken using a swept-source optical coherence tomography-based optical biometer (IOLmaster 700) and an optical low-coherence reflectometry biometer (Lenstar 900), and to determine the clinical impacts of differences in their measurements on intraocular lens (IOL) power predictions.MethodsEighty eyes of 80 patients scheduled to undergo cataract surgery were examined with both biometers. The measurements made using each device were axial length (AL), central corneal thickness (CCT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 15 publications
(17 reference statements)
1
30
2
2
Order By: Relevance
“…This difference is low and clinically not significant. Arriola-Villalobos et al 6 found a statically but clinically significant difference between these two devices.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This difference is low and clinically not significant. Arriola-Villalobos et al 6 found a statically but clinically significant difference between these two devices.…”
Section: Discussionmentioning
confidence: 95%
“…5,6 This rate seems higher with the optical low-coherence reflectometry where the failure rates vary between 5.8% and 16%. [6][7][8][9] This difference can be explained by the higher wavelength used in biometry with the swept-source OCT (1080 vs 820 nm), allowing deeper penetration and less attenuation or diffusion of light when lens opacity is present. For the different noncontact optical biometry technologies, posterior subcapsular cataracts are a source of measurement failure.…”
Section: Discussionmentioning
confidence: 96%
“…5.4 vs. Argos: p = 0.006). Hoffer et al and Villalobos et al also report that the value measured by IOLMaster 700 was significantly smaller than those measured by PCI devices [4, 14]. The difference between the two SS-OCT devices and the PCI device might be due to difference in measurement technique for each type of device.…”
Section: Discussionmentioning
confidence: 99%
“…IOLMaster 700 (Carl Zeiss Meditec), the first SS-OCT-based biometric device, is one of the most widely used devices for cataract surgery [3]. Many studies have shown that IOLMaster 700 had good agreement with other devices, including IOLMaster 500 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%